Coronavirus pandemic (COVID-19) as a force majeure event to fulfill contractual obligations - Fronchko, Volodymyr; Tsomyk, Viktoriia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The peculiarities of the impact of the coronavirus pandemic on the consciousness of society, which led to a change in the structures in civil law agreements, have been studied. Now 2020 is an influential year for big and small businesses, when assessing force majeure, the fulfillment of obligations makes it impossible to act. Pandemic COVID - 19, as a story that will be remembered by everyone from the general population to the leaders, so this article is relevant for comparing civil law contracts at different stages of its existence. Over to force majeure on the territory of Ukraine, the Law "On Amendments to Certain Legislative Acts of Ukraine Aimed at Providing Additional Social and Economic Guarantees in Connection with the Spread of Coronavirus Disease (COVID-19)" was adopted. Force majeure circumstances are extraordinary and unavoidable circumstances that objectively make it impossible to fulfill the obligations under the terms of the agreement (contract, agreement, etc.), obligations under laws and regulations. Force majeure includes various circumstances, including epidemics, the introduction of curfews, mass riots, long breaks in transport, emergencies, restrictions by public authorities, etc. At such a difficult time, we have an important mission to comply with legal rules and world recommendations regarding health care, but we should not forget about fulfilling the obligations established by contract or law. Today we are in a quarantine situation, due to which the majority has lost the opportunity to earn money, which leads to non-fulfillment of civil obligations. The state is trying to make even minimal, but improvements for the public good. The adopted temporary amendments to the laws and by-laws concerning civil law are successful and useful. The new law also regulates other areas and issues, namely: support for the unemployed in quarantine; weakening the tax on enterprises; temporary simplification of production and procedures for their purchase necessary to combat the spread of coronavirus; introduction of remote work and education; support of the employer and the employee in the conditions of quarantine; implementation of social benefits.